Isolevuglandins Scavenger Ameliorates Myocardial Ischemic Injury by Suppressing Oxidative Stress, Apoptosis, and Inflammation - Guo, Junjie; Xu, Fengqiang; Ji, Hongwei; Jing, Yajun; Shen, Li; Weng, Xinyu; Hu, Longgang (Frontiers in Cell and Developmental Biology, 2022)
Augmented levels of reactive isolevuglandins (IsoLGs) are responsible for cardiovascular diseases. The role of IsoLGs in myocardial infarction (MI) remains elusive. Here we explored the effect of IsoLGs scavenger 2-hydroxybenzylamine (2-HOBA) in post-infarction cardiac repair. We observed that infarcted cardiac tissues expressed high IsoLGs in mice. Following MI injury, 2-HOBA treated mice displayed decreased infarction area and improved heart function compared with the saline-treated group. Moreover, 2-HOBA effectively attenuated MI-induced cardiac remodeling, oxidative stress, apoptosis, and inflammation. 4-hydroxybenzylamine (4-HOBA), a less reactive isomer of 2-HOBA, barely antagonized the MI-induced injury. These findings suggest that IsoLGs elimination may be helpful in MI therapy.